2019
DOI: 10.1186/s12888-019-2392-0
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum psychosis in bipolar disorder: no evidence of association with personality traits, cognitive style or affective temperaments

Abstract: BackgroundBipolar disorder has been associated with several personality traits, cognitive styles and affective temperaments. Women who have bipolar disorder are at increased risk of experiencing postpartum psychosis, however little research has investigated these traits and temperaments in relation to postpartum psychosis. The aim of this study is to establish whether aspects of personality, cognitive style and affective temperament that have been associated with bipolar disorder also confer vulnerability to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Psychological and social factors have been shown to be important in the triggering of postpartum depression [45,46]; however, these factors appear to play less of a role in the triggering of postpartum psychosis. Personality traits, cognitive styles or affective temperaments show no specific relationship to postpartum psychosis [47], despite these factors being associated with postpartum depression and with bipolar disorder more generally. The potential relationship between life stressors (such as history of trauma) and the onset of postpartum psychosis has been examined in several studies, yet no consistent associations have been found with adverse life events occurring within pregnancy or the 12 months prior to delivery [48][49][50][51], nor with those occurring during childhood [46,52].…”
Section: Psychological and Social Factorsmentioning
confidence: 83%
“…Psychological and social factors have been shown to be important in the triggering of postpartum depression [45,46]; however, these factors appear to play less of a role in the triggering of postpartum psychosis. Personality traits, cognitive styles or affective temperaments show no specific relationship to postpartum psychosis [47], despite these factors being associated with postpartum depression and with bipolar disorder more generally. The potential relationship between life stressors (such as history of trauma) and the onset of postpartum psychosis has been examined in several studies, yet no consistent associations have been found with adverse life events occurring within pregnancy or the 12 months prior to delivery [48][49][50][51], nor with those occurring during childhood [46,52].…”
Section: Psychological and Social Factorsmentioning
confidence: 83%
“…The possibility of the woman harming the child while she is being treated, as she has a distorted perception of reality, is small, and immediately requires a proper clinical assessment and appropriate manipulations [21]. Based on a study published in 2018 [23], the effect on the development of the infant-mother bond is different between women who had a primary PP and have fully recovered and mothers who developed PP in the context of a lingering severe schizophrenic spectrum disorder. However, an acute episode of PP associated to better mother-infant interlinkages.…”
Section: Effects Of Postpartum Psychosis In Infant's Lifementioning
confidence: 99%
“…Since the 19th century, it has been evaluated as a disease that needs immediate treatment in a psychiatric unit, and has generally good prognosis [2]. The manifestation of PP may occur either as a primary episode or a recurrence of a pre-existing disease, such as Bipolar Disorder (BD) [3]. In both cases, the psychiatric medical family history is taken for granted.…”
Section: Introductionmentioning
confidence: 99%
“…The onset of most postpartum psychosis episodes is within 2 weeks of delivery [ 3 ]. These symptoms develop quickly and dramatically and in the majority of cases require hospitalization [ 4 ].…”
Section: Introductionmentioning
confidence: 99%